A female case report of LGMD2B with compound heterozygous mutations of the DYSF gene and asymptomatic mutation of the X-linked DMD gene - Cao, Xiaojie; Zeng, Li; Lu, Zhijie; Fan, Jin; Tan, Song; Zhang, Mingjie; Yin, Zegang (Frontiers in Neurology, 2023)
We report the case of a 31-year-old Chinese woman with a chief complaint of weakness in the lower limbs, which was diagnosed as limb-girdle muscular dystrophy 2B (LGMD2B) with compound heterozygous mutations of the DYSF gene. Meanwhile, this woman is an asymptomatic carrier with the mutation of the X-linked DMD gene. The electromyography, muscle MRI, and muscle biopsy indicated a chronic myogenic injury with dysferlin deletion. As a result of genetic testing, compound heterozygous G-to-T base substitution at position 5,497 in exon 49 of the DYSF gene, leading to a codon change from glutamic acid to termination codon at position 1,833, and a heterozygous C-to-G base change at position 4,638 + 8 in intron 42 of the DYSF gene with a consequence of splice, which has never been reported, were identified as candidate causative mutations. Unfortunately, DMD gene mutation c.3921+12A>G of the DMD gene on the X chromosome was also found in this patient. Finally, the patient was diagnosed as LGMD2B clinically and genetically. In the previous 2 years, the patient's lower limb weakness became slightly worse, resulting in even the total distance walked than before. Fortunately, during the follow-up, her son had not shown slowness or limitation of movement. Genetic testing by next-generation sequencing confirmed the final diagnosis of LGMD2B, and we identified the novel compound heterozygous variants in the DYSF gene, which is of great significance to the accurate diagnosis of genetically coded diseases. Much attention needs to be paid in clinics toward hereditary neuromuscular diseases with multiple pathogenic gene mutations. Genetic counseling and clinical follow-up should be the priorities in future, and promising treatments are also worth exploring.